The impact of nail psoriasis on disease activity, quality of life, and clinical variables in patients with psoriatic arthritis: A cross‐sectional multicenter study. (27th September 2022) - Cengiz, Gizem; Nas, Kemal; Keskin, Yaşar; Kılıç, Erkan; Sargin, Betül; Acer Kasman, Sevtap; Alkan, Hakan; Sahin, Nilay; Cüzdan Balta, Nihan; Gezer, İlknur Albayrak and Keskin, Dilek and Mülkoğlu, Cevriye and Reşorlu, Hatice and Ataman, Şebnem and Bal, Ajda and Baykul, Merve and Duruöz, Mehmet Tuncay and Küçükakkaş, Okan and Yurdakul, Ozan Volkan and Alkan Melikoğlu, Meltem and Ayhan, Fikriye Figen and Bodur, Hatice and Çaliş, Mustafa and Çapkin, Erhan and Devrimsel, Gül and Gök, Kevser and Hizmetli, Sami and Kamanlı, Ayhan and Ecesoy, Hilal and Kutluk, Öznur and Şen, Nesrin and Şendur, Ömer Faruk and Tekeoğlu, İbrahim and Toprak, Murat and Tolu, Sena and Tuncer, Tiraje
Abstract: Aim: Nail involvement is common in psoriatic arthritis. This study assesses clinical characteristics, nail psoriasis prevalence, and impact of nail psoriasis on disease activity in patients with psoriatic arthritis (PsA). Method: This cross‐sectional multicenter study was conducted by the Turkish League Against Rheumatism using PsA patients recruited from 25 centers. Demographic and clinical characteristics of PsA patients, such as disease activity measures, quality of life, and nail involvement findings were assessed during routine follow‐up examinations. Patients were divided into two groups according to the presence or absence of nail psoriasis and compared using the χ 2 test or Fisher exact test for categorical variables and the t‐test or Mann‐Whitney U test for continuous variables. Results: In 1122 individuals with PsA, 645 (57.5%) displayed nail psoriasis. The most frequent features of fingernails were ridges (38%), followed by pitting (21%) and onycholysis (19%). More females were present in both groups (with and without nail psoriasis; 64% vs 67%, P < 0.282). Patients with nail psoriasis were older, indicated more pain and fatigue, experienced greater swelling, tender joint counts, and skin disease severity, and had a higher disease activity score compared with those without nail psoriasis (all P < 0.05). Conclusion: We demonstrate an increased prevalence of nail psoriasis observed in patients with psoriatic arthritis. Patients with nail involvement experience increased disease activity, lower quality of life, and diminished mental and physical status compared with those without nail involvement.